A critical evaluation of South Africa's enactment of new anti-trafficking legislation in fulfilment of its international obligations to prevent, suppress and combat the trafficking of persons under the Palermo Convention - Pretorius, Nandi (Stellenbosch : Stellenbosch University, 2020)
Thesis (LLM)--Stellenbosch University, 2020.